The surgical strategy of hormonally active primary cardiac paraganglioma sarcoma: A case report - Wang, Xiangyu; Liu, Haiyuan; Zhang, Shuaipeng; Huang, Shaojun; Zhang, Chengxin (Frontiers in Cardiovascular Medicine, 2022)
Cardiac paraganglioma is a kind of rare neuroendocrine tumor characterized with persistent secretion of catecholamines. Under excessive exposure of catecholamines, some atypical symptoms are presented including hypertension, arrhythmias, and headache. The surgical treatment of a 28-year-old female case with primary cardiac paraganglioma is presented for experience sharing and surgical skill improvements.